Effect of Rheological on the Physical and Electrical Properties of Extruded Micro Carbon -LLDPE Composites - Agus Edy Pramono; Aminudin Zuhri; Iman Setyadi; Nanik Indayaningsih (Recent in Engineering Science and Technology, 2024)
This study focuses on formulating and optimizing a conductive polymer composite (CPC) material tailored for electromechanical applications. Linear Low-Density Polyethylene (LLDPE) polymer and micro carbon particles derived from rice husk were compounded using a hot compaction process and melt blended through a single-screw extrusion machine. A mix of 50% loading of microcarbon particles was used in this research. It was determined that the experiment was successfully conducted, resulting in a stabilized density of approximately 1 g/cm³. The research demonstrates how the prototype Extruder Head effectively stabilizes the density of composites. Electrical conductivity demonstrated a notable increase in conductivity toward higher density. These findings underscore the successful development of a CPC material with improved electrical conductivity, making it a highly suitable tool for high carbon-loading composite material.